Guibourtia tessmannii-induced fictive ejaculation in spinal male rat: involvement of D1, D2-like receptors - Patrick Brice Deeh Defo; Elvis Asongu; Modeste Nya Wankeu; Esther Ngadjui; Georges Romeo Bonsou Fazin; François Xavier Kemka; Miguel Carro-Juarez; Albert Kamanyi; Pierre Kamtchouing; Pierre Watcho (Taylor & Francis Group, 2017)
Context: Guibourtia tessmannii (Caesalpiniaceae) is a plant traditionally used as aphrodisiac. We previously reported the pro-ejaculatory effects of the aqueous and methanol extracts of G. tesmannii in spinal male rat. However, the mechanism underlying such effects has not been elucidated. Objective: This study characterizes the dopaminergic sub-type receptors involved in G. tesmannii-induced ejaculation in male Wistar rat. Materials and methods: Urethane-anesthetized spinal male rats were intravenously treated with saline solution (1 mL/kg, control); dopamine (0.1 μmol/kg, reference); aqueous or methanol extracts of G. tesmannii (20 mg/kg) in the absence or presence of haloperidol (0.26 μmol/kg), a nonspecific dopaminergic receptor antagonist, Sch23390 (0.26 μmol/kg), a specific D1-like receptor antagonist or, sulpiride (0.26 μmol/kg), a specific D2-like receptor antagonist. Electromyography of the bulbospongiosus muscles and intraseminal pressure were recorded after urethral, penile and drug stimulations. Results: Urethral and penile stimulations, intravenous injection of dopamine or, aqueous and methanol extracts of G. tesmannii always triggered the expression of rhythmic contraction of the bulbospongiosus muscles with an average mean of 3.33 ± 0.43; 7.83 ± 0.85; 9.80 ± 0.86; 0.83 ± 0.54 and 2.67 ± 0.95 contractions, respectively. The intraseminal pressure was more expressed after urethral and penile stimulations (15.66 ± 1.58 and 13.60 ± 2.40 mmHg, respectively). In rats pretreated with haloperidol, Sch23390 or sulpiride, no ejaculation was recorded after intravenous injection of G. tesmannii extracts or dopamine. Discussion and conclusion: Guibourtia tesmannii-induced ejaculation requires the integrity of D1 and D2-like receptors. These findings further justify the ethno-medicinal claims of G. tesmannii as an aphrodisiac.